Group Guidance Strategies to Develop Social Skills in Adolescents: A Literature Review - Nurhasanah, Enung; Sudatha, I Gede Wawan; Santosa, Made Hery; Suartama, I Kadek (Journal of English Language and Education, 2025)
The development of social skills in junior high school students is a vital component in fostering social-emotional competence, supporting academic achievement, and promoting long-term social adjustment. In light of the growing prevalence of social issues such as bullying, social anxiety, and limited healthy interactions within school environments, group guidance services must adopt more innovative, adaptive, and contextually relevant approaches. This urgency highlights the need for a systematic review of effective group guidance strategies aimed at enhancing students' social skills. This study aims to identify and evaluate innovative strategies in group guidance services through a Systematic Literature Review (SLR). The review analyzes peer-reviewed articles published between 2018 and 2024, sourced from reputable academic databases including Scopus, ERIC, and Web of Science. A thematic analysis approach is used to examine the effectiveness of various strategies, key components of service delivery, implementation contexts across countries, and their impacts on different dimensions of social skills. The findings reveal that strategies based on experiential learning, role-playing, interactive media, and collaborative activities significantly contribute to improving students' communication, empathy, cooperation, and conflict resolution abilities. Furthermore, the results highlight the critical role of group structure, facilitator competence, and the integration of relevant theoretical frameworks in designing effective group guidance programs.